1985
DOI: 10.1126/science.230.4726.674
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatins: The Principal Heavy-Metal Complexing Peptides of Higher Plants

Abstract: A set of novel heavy-metal complexing peptides was isolated from plant cell suspension cultures; the structure of the peptides was established as (gamma-glutamic acid-cysteine)n-glycine (n = 3 to 7). These peptides appear upon induction of plant cells with heavy metals and represent the principal metal-binding activities in the cells. The name phytochelatin is proposed for this new class of natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
605
0
22

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,128 publications
(640 citation statements)
references
References 14 publications
13
605
0
22
Order By: Relevance
“…Previous studies have reported Cd-induced PC synthesis (Grill et al, 1985;Ranieri et al, 2005;Wang and Wang, 2011) and identified Cd 2+ -PC n complexes either under laboratory conditions (Kobayashi and Yoshimura, 2006;Chekmeneva et al, 2007; or from plants in their native environment (Scarano and Morelli, 2002;Chen et al, 2007) as evidence for the proposed mechanism (Sanità di Toppi and Gabbrielli, 1999) involved in Cd detoxification in plants.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have reported Cd-induced PC synthesis (Grill et al, 1985;Ranieri et al, 2005;Wang and Wang, 2011) and identified Cd 2+ -PC n complexes either under laboratory conditions (Kobayashi and Yoshimura, 2006;Chekmeneva et al, 2007; or from plants in their native environment (Scarano and Morelli, 2002;Chen et al, 2007) as evidence for the proposed mechanism (Sanità di Toppi and Gabbrielli, 1999) involved in Cd detoxification in plants.…”
Section: Introductionmentioning
confidence: 98%
“…Phytochelatins (PCs) are enzymatically synthesized peptides in plants that usually consist of three amino acids: glutamic acid (Glu), cysteine (Cys) and glycine (Gly) (Kondo et al, 1984;Grill et al, 1985). The resultant glutathione (GSH) molecule (γ-Glu-Cys)-Gly is transformed into PC by γ-glutamylcysteine dipeptidyl transpeptidase (phytochelatin synthase, EC 2.3.2.15), forming the general structural formula of (γ-Glu-Cys) n -Gly, where n ranges from 2-11 (Grill et al, 1985;1987;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are enzymatically biosynthesized in plants as a defense mechanism to cope with the stress of toxic heavy metal ions such as Cd 2+ , Pb 2+ , Ag + , and Hg 2+ , [1] as well as metalloid species such as Sb 3+ , AsO 4 − , and SeO 3 2− . Originally, biosynthesis of PCs was thought to be activated by the binding of heavy metal ions to the enzyme PC synthase, a heavy metal-activated enzyme, and terminated by sequestration of heavy metal ions by the PCs [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numeral researches have been reported that in response to toxicity of heavy metals plants could produce many kinds of reactive oxygen species, antioxidant enzyme (Rodriguez-Serrano et al, 2006;Stohs and Bagchi, 1995), glutathione (GSH) (Howden et al, 1995;Nocito et al, 2006;Sun et al, 2005), phytochelatins (PCs) (Cobbett, 2000;Grill et al, 1985;Mishra et al, 2006;Stolt et al, 2003), and other complex ligands (de la Rosa et al, 2004;Isaure et al, 2006;Zhang et al, 2004). The detoxification ways of heavy metals in plant tissues include speciation of metal with organic ligands and elimination of oxidative stress through the function of antioxidant reaction.…”
Section: Introductionmentioning
confidence: 99%